Kaikki irti metsästä : metsän käyttö ja muutos taigan reunalla itäisimmässä Suomessa erätaloudesta vuoteen 2000 - Björn, Ismo (Suomen Historiallinen Seura, 1999)
Summary: Capitalizing on the forest : use, users and change in the forest in the wilderness economy on the edge of the taiga in Eastern Finland through the year 2000